(untitled) (Research, Society and Development, 2020)
The objective of the study was to identify the questionnaires used to assess fatigue in workers. A systematic review was carried out in the MEDLINE/PubMed and LILACS databases. Of the 407 studies found, 21 met the selection criteria. Seven questionnaires were identified to assess fatigue in workers who have been translated and adapted to Portuguese and have been validated in the country, they are: Yoshitake Fatigue Questionnaire; Bipolar Questionnaire Assessment of Fatigue; Chalder’s Fatigue Scale; Need for Recovery Scale; Checklist of Individual Strength; Multidimensional Assessment of Fatigue Scale and Fatigue Severity Scale. The metrics of each of them were discussed, observing their differences. It was identified that the questionnaires complement each other, as it was not found a questionnaire that separates physical and mental fatigue and that also verifies the intensity of fatigue. Thus, it is suggested to use more than one questionnaire in research involving this theme, in order to cover different perspectives of fatigue assessment.